2006
DOI: 10.1002/jor.20145
|View full text |Cite
|
Sign up to set email alerts
|

Density and structural changes in the bone of growing rats after weekly alendronate administration with and without a methotrexate challenge

Abstract: Alendronate (ALN) and other bisphosphonates have been used successfully in pediatric patients with osteopenia secondary to connective tissue diseases. Loss of growth in height has not been reported, but concerns remain regarding the effect of these potent antiresorptive agents when used in children and adolescents. High-dose methotrexate (MTX) and other chemotherapy drugs have been implicated in osteoporosis and a high fracture incidence in survivors of childhood cancers and are also associated with osteopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(72 reference statements)
1
6
0
2
Order By: Relevance
“…Indeed, in our experiments, ZA increased BMD and improved all histomorphometric parameters. These results are consistent with those of Spadaro and colleagues, who found that alendronate prevented bone loss induced by high-doses of MTX treatment in rats [39]. Other bisphosphonates, such as alendronate, have also been shown to be effective in the prevention of systemic bone loss associated with RA during treatment with MTX [40] or corticosteroids [11].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in our experiments, ZA increased BMD and improved all histomorphometric parameters. These results are consistent with those of Spadaro and colleagues, who found that alendronate prevented bone loss induced by high-doses of MTX treatment in rats [39]. Other bisphosphonates, such as alendronate, have also been shown to be effective in the prevention of systemic bone loss associated with RA during treatment with MTX [40] or corticosteroids [11].…”
Section: Discussionsupporting
confidence: 89%
“…The limited number of studies using OVX rabbits makes it difficult to conclude whether the lack of a large decline in bone strength in response to estrogen deficiency applies to this species in general. Strong and positive effects of ALN on bone density, bone strength, and fracture risk in human and other species have been widely acknowledged 26–29. Interestingly, these studies demonstrated that a higher dose of ALN (200 to 600 µg/kg/week s.c.) was needed to protect against OVX‐induced bone loss in the rabbit than in rat and other species 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent experiment showed increased trabecular bone volume following seven days of subcutaneous (SC) alendronate (ALN) (0.010 mg/kg/d) [18]. Furthermore, a more recent study using weanling rats showed an increase in distal femoral metaphyseal BMD following six weeks of once-weekly treatment with ALN [19]. A higher growth rate of the distal and proximal femur, the proximal tibia, and the proximal and distal radius has been observed in the rapidly growing rabbit than that typically observed with other species or in more mature animals [20,21].…”
Section: Introductionmentioning
confidence: 99%